Cervicovaginal Fungi and Bacteria Associated With Cervical Intraepithelial Neoplasia and High-Risk Human Papillomavirus Infections in a Hispanic Population - Godoy-Vitorino, Filipa; Romaguera, Josefina; Zhao, Chunyu; Vargas-Robles, Daniela; Ortiz-Morales, Gilmary; Vázquez-Sánchez, Frances; Sanchez-Vázquez, Maria; de la Garza-Casillas, Manuel; Martinez-Ferrer, Magaly; White, James Robert; Bittinger, Kyle; Dominguez-Bello, Maria Gloria; et al. (Frontiers in Microbiology, 2018)
The human cervicovaginal microbiota resides at an interface between the host and the environment and may affect susceptibility to disease. Puerto Rican women have high HPV infection and cervical cancer rates. We hypothesized that the population structure of the cervicovaginal bacterial and fungal biota changed with cervical squamous intraepithelial lesions and HPV infections. DNA was extracted from cervix, introitus and anal sites of 62 patients attending high-risk San Juan clinics. The 16S rRNA V4 region and ITS-2 fungal regions were amplified and sequenced using Illumina technology. HPV genotyping was determined by reverse hybridization with the HPV SPF10-LiPA25 kit. HPV prevalence was 84% of which ~44% subjects were infected with high-risk HPV, ~35% were co-infected with as many as 9 HPV types and ~5% were infected with exclusively low-risk HPV types. HPV diversity did not change with cervical dysplasia. Cervical bacteria were more diverse in patients with CIN3 pre-cancerous lesions. We found enrichment of Atopobium vaginae and Gardnerella vaginalis in patients with CIN3 lesions. We found no significant bacterial biomarkers associated with HPV infections. Fungal diversity was significantly higher in cervical samples with high-risk HPV and introitus samples of patients with Atypical Squamous Cells of Undetermined Significance (ASCUS). Fungal biomarker signatures for vagina and cervix include Sporidiobolaceae and Sacharomyces for ASCUS, and Malassezia for high-risk HPV infections. Our combined data suggests that specific cervicovaginal bacterial and fungal populations are related to the host epithelial microenvironment, and could play roles in cervical dysplasia.